Music students’ workload, stress, and coping in higher education: Evidence-based policymaking - Jääskeläinen, Tuula (Frontiers in psychology, 2022)
Evidence-based policies are needed to support students as they cope with their experiences of workload and stress in higher music education. This subject was explored in the Music Student Workload Project as a collaboration between Finland and the United Kingdom in seven studies: (1) a theoretical study scrutinizing diverse higher music education systems in connection with equality and cultural reproduction; (2) a systematic review mapping international research on music students’ workload; (3) a methodological study discussing the transcendental phenomenological approach as a method for obtaining a meaningful understanding of music students’ experiences in higher education; (4) a qualitative study exploring music students’ workload experiences in connection with their meaningful engagement in music; (5) a mixed-method study shedding light on music students’ proactive coping styles in connection with workload and stress; (6) a mixed-method study examining music students’ experienced workload, stress, and livelihoods; and (7) a qualitative study exploring teachers’ ways of supporting music students’ workload and stress. The meta-narrative synthesis was conducted by triangulating the key elements of these studies to generate four actionable policy and intervention recommendations to inform educational policies and practices for supporting students in coping with workload and stress in higher music education: (1) support music students’ proactive coping skills; (2) find solutions to the unequal workload and stress experiences between low-income and well-off students, different genders, and different study programs; (3) ensure teachers’ continuing professional development, particularly in the learner-centered pedagogical approaches; and (4) invest resources for providing more longitudinal, cross-cultural, and interventional research investigating music students’ discipline-specific experiences of workload and stress.